2010
DOI: 10.5005/jp-journals-10018-1186
|View full text |Cite
|
Sign up to set email alerts
|

Role of Renin–Angiotensin-converting Enzyme Level and ACE Gene Polymorphism in Patients with Nonalcoholic Fatty Liver Disease

Abstract: IntroductionIn this study, we aimed to investigate the histological and clinical effect of angiotensin-converting enzyme (ACE) and ACE gene polymorphism in nonalcoholic fatty liver disease (NAFLD) and their roles in the progression of the disease.Materials and methodsLiver function tests, body mass index, waist circumference, lipid parameters, fasting blood glucose (FBG), hemoglobin A1c (HbA1c), homeostasis model assessment-IR (HOMA-IR), ACE, and ACE gene polymorphism were evaluated in the NAFLD group and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…[ 19 ] who showed no marked influence of the ACE I/D polymorphism on EP necessity in hemodialysis individuals. On the other hand, our findings contradict two recent studies that included continuous ambulatory peritoneal dialysis people and found that the ACE II/ID genotypes are linked to inadequate EP response [ 20 , 21 ]. These findings' variances are attributed to the ethnic differences between people.…”
Section: Discussioncontrasting
confidence: 98%
“…[ 19 ] who showed no marked influence of the ACE I/D polymorphism on EP necessity in hemodialysis individuals. On the other hand, our findings contradict two recent studies that included continuous ambulatory peritoneal dialysis people and found that the ACE II/ID genotypes are linked to inadequate EP response [ 20 , 21 ]. These findings' variances are attributed to the ethnic differences between people.…”
Section: Discussioncontrasting
confidence: 98%
“…Till now, the complete pathogenesis is not confirmed (Zhang et al, 2019). There are limited studies have been recorded with NAFLD in the global population and showed both significant and non-significant association (Güçlü et al, 2010;Tekatas et al, 2016;Sydorchuk et al, 2018). Our study is also in agreement with the previous studies, which showed a negative association (P>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The ACE gene insertion/deletion (I/D) polymorphism denotes the appearance or disappearance of 287bp of Alu sequence present at the intron 16 region (Khan et al, 2014). Limited studies have been documented in the NAFLD with ACE gene I/D polymorphism (Tekatas et al, 2016;Sydorchuk et al, 2018;Güçlü et al, 2010). There are no documented studies have been stated in the Saudi population between I/D polymorphism in the ACE gene.…”
Section: Introductionmentioning
confidence: 99%